IMPROVEMENT OF METHODS OF LIFETIME DIAGNOSTIC OF SARCOPTOSES, DEMODECOSES AND OTODEKTOSES OF DOGS - Євстаф’єва, В. О.; Гаврик, К. А. (Scientific Progress & Innovations, 2014)
The article presents the results of the determination of indicators of diagnostic efficiency of lifetime diagnostic methods akarosis of dogs, namely: sarcoptoses, demodecoses and otodektoses. Comparing methods of Priselkova and Alfimova and an improved our way. It is found that the proposed improved method for the diagnosis of sarcoptoses, otodektoses and demodecoses of dogs has a high diagnostic efficiency (5–40 %) than well-known methods, and does not require time consuming and provides a high degree of bleaching crusts and sharpness of the obtained material.